Long-term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - LIMOUSIN, J. M.; Rambal, S.; OURCIVAL, J. M.; Rocheteau, A.; JOFFRE, R.; RODRIGUEZ-CORTINA, R. (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4-year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well-watered periods. Despite a tight stomatal control over transpiration, whole-tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought; ecohydrology; Hydraulic conductance; leaf area index; leaf water potential; Mediterranean evergreen forest; Quercus ilex; throughfall exclusion; Transpiration